STUDY ON THE BASIS OF COMPUTER MODEL OF STEEL HEATING PROCESS IN ORDER TO REDUCE RESOURCE COSTS (Computer systems and information technologies, 2023)
Steel is one of the most important materials in the modern world, used in various industries and construction. Steel production starts with heating steel melt in steel ladles, the equipment used in the steel industry to produce various types of steel. The ladle plays a key role in this process, as it is the place where the steel melt is heated. The search for rational technological layouts that ensure the economical use of material and energy resources in the manufacture of high-quality steel products is an urgent scientific and technical challenge facing the engineering staff of steelmaking and high-quality competitive steel products. Random increases and decreases in steel temperature can lead to deterioration in steel quality, accelerated erosion of refractory materials, and increased energy consumption. Steel heat losses depend on the ladle's thermal state, thermal and physical properties of the steel, and slag. The thermal state and thermal properties of molten steel and slag need to be quantified to better control the production process, the final steel composition, and the desired pouring temperature.
Keywords: computational fluid dynamics; melt; cost reduction; steel ladle